Software simulation as educational tool - Lasić-Lazić, Jadranka (Array, 2011)
One of main aims of computer science education is to train students to perform certain tasks by computers. raditionally this is carried out by demonstration method, where teacher demonstrates to students how to use certain application. It is very difficult to achieve individualization of teaching when using this teaching method, because teacher has limited time for demonstration and students usually have very heterogeneous knowledge. Software simulation can provide significant help in training students to use computer applications, because they can be used to demonstrate to students how to perform certain tasks in software, students can then practice that tasks in software simulator and, finally, software simulation can be used to assess student’s knowledge. Software simulation allows great level of individualization, because students can progress at pace that suits them, they can repeat demonstration several times and they can practice task until they are confident that they have mastered it. This paper presents model for integration of software simulation as teaching method into computer science curriculum.